Języki regionalne w systemie narodowej edukacji Indonezji: Studia porównawcze nad programami nauczania języka jawajskiego, sundajskiego i dajak - Gumilar, Teija (Investigationes Linguisticae, 2016)
Indonesian language has been a lingua franca between 1.128 ethnical groups speaking 746 regional languages and dialects, living in the Republic of Indonesia. The domination of Indonesian language in daily practice, the emerging popularity of foreign languages and the change in socio-economic condition have adverse impacts to the existence of regional languages. By 2007 about 35% of those languages are believed to be disappearing. Some ethnical groups with large population succeeded developing their languages through elaborate standardization, better teaching programs and rich literary works. Since 2004 government and linguists have been working on effective regional languages teaching and promotion programs. As the educational policy lies in the hand of provincial government, new strategies have been implemented to incorporate regional language teaching into local content subjects within elementary, secondary and high schools respectively. In this paper the author will show a comparison study between teaching programs of Javanese, Sundanese and Dayak languages.